Interviewing and salary negotiation for job hunters, career changers, consultants, and freelancers - Wendleton, Kate (Career Press, 1999)
Based on years of experience helping job hunters land the best jobs at the best pay, Kate Wendleton presents all the latest proven strategies for maximizing the interview and salary negotiation process. Readers learn solid communication skills for effective negotiation and follow-up, as well as tips and tricks that navigate the most difficult interview questions and situations